DEMAND FOR TEACHING FOREIGN LANGUAGES IN THE MODERN EDUCATION SYSTEM AND INNOVATIVE METHODS OF TEACHING ENGLISH LANGUAGE - Sanjarova Aziza Arzikul kizi (American Journals, 2023)
This article describes several methods of effective teaching of English, and more foreign languages as well as some of the modern educational technologies, innovations used in language and its learning.
Keywords: Language, English, independent language learning, educational technologies , project, interest, activity, interactive methods.